ChemInform Abstract: Preparation of Esters and Amides from Carboxylic Acids and N‐Formylation of Amines Promoted by 1, 3, 5‐Triazo‐2, 4, 6‐triphosphorine‐2, 2, 4, 4, 6, 6‐hexachloride (TAPC). Issue 52 (24th December 2013) - Bahrami, Kiumars; Khodaei, Mohammad M.; Targhan, Homa; Sheikh Arabi, Mehdi
Abstract A simple and new procedure is described to synthesize a variety of carboxylic esters by using TAPC as an effective promoter.